Policy Reflection: Kurikulum Merdeka as Educational Innovation in the Era of Society 5.0 - Langoday, Yohanes Redan; Nurrahma, Nurrahma; Rijal, Syamsul (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Kurikulum Merdeka represents Indonesia's strategic response to the demands of Society 5.0, an era marked by pervasive technology integration. As an educational innovation, it aims to cultivate future-ready individuals adept at utilizing technology, possessing competitiveness, and providing innovative solutions for society. The curriculum emphasizes developing 21st century skills like critical thinking, creativity, and digital literacy through student-centered, project-based learning and formative assessments. Key opportunities include nurturing an adaptable, tech-savvy workforce and aligning education with industry needs. However, challenges arise in teacher readiness for constructivist pedagogy, technological competence, and the need for continuous curriculum updates. Successful implementation requires enhancing teacher training, providing adequate technological infrastructure, and fostering multi-stakeholder collaboration in curriculum design and evaluation. Policy reflection is crucial to optimize Kurikulum Merdeka's responsiveness to Society 5.0's rapid changes. By addressing opportunities, overcoming obstacles, and ensuring industry relevance, Indonesia can effectively prepare its youth to thrive in an increasingly digitalized world while driving sustainable societal progress. Proactive policy measures can position the education system as a catalyst for innovation and human capital development in the Society 5.0 landscape..